Failing Despite Knowing. Repeated Decision-Making During Binary Random Sequences with Asymmetric Probabilities - Uatkán Ajna; Ruzsa Gábor; Faragó Klára (Open Psychology)
Previous research shows that people often misinterpret randomness, expecting short-term outcomes to balance out, known as negative recency. Most studies have focused on binary events with equal odds (1:1). This study uniquely examines risk-taking behaviour in an asymmetric setup with 2:1 odds. In two studies, we examined risk-taking behaviour of 178 and 55 participants, respectively, across two investment simulations, whereby individuals had to make sequential decisions (10 × 10 times) about how much money to invest in two kinds of risky shares, alternating randomly over 10 imaginary days: the winner type, with odds 2:1 of winning vs losing, and the loser type, with odds reversed. We analysed correlations of invested amounts with the signed run length and the posterior probability of trading with the "winner” type share, respectively. The first correlation captures the effect of the belief in the run continuing or reversing, and the second one is considered an indicator of economically rational decision-making. Despite the asymmetric setup, 29 and 31% of participants followed maladaptive strategies. Among them, 14 and 7 participants lost all their money before the simulation ended. These findings underscore the detrimental impact of negative recency, leading to significant financial losses and reduced gains.